2020
DOI: 10.1371/journal.pone.0241144
|View full text |Cite
|
Sign up to set email alerts
|

Moral “foundations” as the product of motivated social cognition: Empathy and other psychological underpinnings of ideological divergence in “individualizing” and “binding” concerns

Abstract: According to moral foundations theory, there are five distinct sources of moral intuition on which political liberals and conservatives differ. The present research program seeks to contextualize this taxonomy within the broader research literature on political ideology as motivated social cognition, including the observation that conservative judgments often serve system-justifying functions. In two studies, a combination of regression and path modeling techniques were used to explore the motivational underpi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 70 publications
(134 reference statements)
3
22
0
Order By: Relevance
“…For example, both of these constructs predicted identification with (powerful, high status) governments and anger at (low‐power, low‐status) citizen protestors in foreign countries, and reduced intention to engage in collective action on behalf of such protestors (Saeri et al., 2015). The current work suggests the predictive effects of these constructs might be partially mediated via increased binding or reduced individualizing endorsement, consistent with arguments that moral foundations reflect motivated cognition (Kugler et al., 2014; Strupp‐Levitsky et al., 2020). The current findings also suggest the predictive patterns in Saeri and colleagues may flip if those protesting reflect a powerful dominant group (e.g., wealthy business owners).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…For example, both of these constructs predicted identification with (powerful, high status) governments and anger at (low‐power, low‐status) citizen protestors in foreign countries, and reduced intention to engage in collective action on behalf of such protestors (Saeri et al., 2015). The current work suggests the predictive effects of these constructs might be partially mediated via increased binding or reduced individualizing endorsement, consistent with arguments that moral foundations reflect motivated cognition (Kugler et al., 2014; Strupp‐Levitsky et al., 2020). The current findings also suggest the predictive patterns in Saeri and colleagues may flip if those protesting reflect a powerful dominant group (e.g., wealthy business owners).…”
Section: Discussionsupporting
confidence: 86%
“…Colin Kaepernick and BLM protests draw attention to racial injustices, including police use of disproportionate force against communities of colour, which question the validity of the status quo in America—for example, questioning whether police and government authorities have the best interests of everyone in mind. Such protests, by challenging the status quo, clash with binding foundation concerns related to loyalty and authority and threaten motivated reasoning to view existing social structures as fair and legitimate (Strupp‐Levitsky et al., 2020). As Fox News Commentator Brad Todd said, Kaepernick is “giving up” during a song saying, “America will endure,” highlighting the perceived threat to traditional values.…”
Section: Discussionmentioning
confidence: 99%
“…The MFT, however, has been criticized on several grounds and, most relevant for the aims of the present work, it has been suggested that binding foundations merely reflect resistance to change and rightwing authoritarianism (RWA), whereas individualizing foundations would reflect SDO and PLOS ONE opposition to equality [52-55; but see 56]. Accordingly, moral intuitions would not be a primary cause of political ideology, but they should be better conceived as a further outcome of motivated social cognition [57,58]. Within this overall framework, it thus becomes important to explore whether parents' moral foundations can end to be further relevant predictors of their children's inequality aversion.…”
Section: The Antecedents Of Inequality Aversionmentioning
confidence: 99%
“…Thus, ideologies and moralities are deeply intertwined, and both are deeply linked to emotion, which is key to forming and maintaining assemblages (Ghoddousi & Page, 2020). While moral codes may include deference to authority, some stem from more “empathic forms of motivation” such as “fairness and the avoidance of harm;” that is, “social justice” (Strupp‐Levitsky et al, 2020, p. 6, 15). Individual decision‐makers’ perceived interests, and associated decisions, may reflect their identity group’s morality (Mann, 2013), or may be grounded in their own empathy – the “ability to feel whatever another person is feeling” (Haidt, 2003, p. 862) – especially toward those they view as vulnerable (Horowitz, 2013).…”
Section: Interest‐convergence Elite Assemblages and Indigenous Cultur...mentioning
confidence: 99%